2019
DOI: 10.2166/washdev.2019.196
|View full text |Cite
|
Sign up to set email alerts
|

Habitations, villages, and gram panchayats: local drinking water planning in rural India with a Pune district case study

Abstract: Improving rural drinking water services at the village level is a high priority in India. The National Rural Drinking Water Program (NRDWP) calls for village drinking water plans on an annual basis. However, planning data analysis and mapping are complicated by the different levels of local settlement that are involved. The aims of this paper are: first, to review how the term ‘village’ has come to refer to three different types of settlement for planning purposes in India; second, to show how each settlement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…There are also myriad smaller habitations (e.g., wadis). The dynamics among these local village levels of settlement have also been complex (Wescoat et al 2019). In general, this paper shows that they have had a strongly hierarchical structure, though history records significant instances of scale-jumping, as for example when the central state sought to connect directly with gram panchayats in the NRDWP.…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 88%
“…There are also myriad smaller habitations (e.g., wadis). The dynamics among these local village levels of settlement have also been complex (Wescoat et al 2019). In general, this paper shows that they have had a strongly hierarchical structure, though history records significant instances of scale-jumping, as for example when the central state sought to connect directly with gram panchayats in the NRDWP.…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 88%
“…That said, research at the village scale identified several planning challenges, including complications in the meaning of the term "village", which as noted above has three main uses in India [39]. The gram panchayat is the most local level of official government in India.…”
Section: Village Scalementioning
confidence: 99%
“…In recent decades, GIS shapefiles have been prepared for revenue villages, which are indeed the only local shapefiles available on an all-India basis. Mapping was shown to be a valuable and largely untapped asset for drinking water planning, but it requires strategies for linking revenue village data with gram panchayat planning needs [39]. The third and smallest meaning of the word village refers to habitations or wadis.…”
Section: Village Scalementioning
confidence: 99%
See 1 more Smart Citation
“…While more frequent estimates are made for drought-affected villages to provide a basis for state intervention, those figures are also estimated rather than measured. Other relevant data, e.g., water quality, are reported at the habitation rather than the village level which has limited their use in geographic information system (GIS) mapping (see Wescoat et al, 2019). Most importantly for this paper, basic parameters of community water service are not collected.…”
Section: The Evolving Situation In Indiamentioning
confidence: 99%